A performance comparison of series power flow control structures in a smart microgrid - Qusay Salem; Khaled Alzaareer; Salman Harasis (Institute of Advanced Engineering and Science, 2022)
This paper investigates the performance of various power control structures on a series power flow controller comprised as transformerless H-bridge inverter under different operating conditions. This power flow controller connects the main grid with the microgrid as it is seriesly attached with the distribution line. Three different control strategies are implemented to regulate the power flow at the interface point using the series power flow controller. The feasibility of the regulation approaches is verified by varying the modulation index and the reference DC-link voltage during different operation modes. Also, the performance of the control strategies is verified under load divergence condition during two different operation modes. The results showed the efficacy of the developed regulation methods in injecting series voltage at point of common coupling (PCC) either during the capacitive or the inductive operation mode. Also, the obtained results reveal the stability and reliability of the regulation methods and the microgrid operation when either the reference DC-link voltage or the modulation index are increased.